The preparation of different pairs near-ultraviolet AlGaN/GaN DBRs with AlN interlayer. (15th June 2018) - Li, Pengchong; Han, Xu; Yan, Long; Deng, Gaoqiang; Liu, Mingzhe; Zhang, Yuantao; Zhang, Baolin
Abstract: In this paper, near-ultraviolet AlGaN/GaN distributed Bragg reflectors (DBRs) were prepared on GaN/sapphire templates by metal organic chemical vapor deposition. A single low-temperature AlN interlayer was adopted to prevent the formation of cracks in DBRs. Moreover, different pairs of DBRs with AlN interlayer were grown to investigate the stress distribution through the epilayer, the surface morphology evolution and the variation of reflectivity spectra. The in-situ stress monitoring shows a compressive-to-tensile stress transition with the increase of DBRs pairs. The optical microscope and atomic force microscope images show that the AlN interlayer induces the appearance of trenches on the surface of DBRs and the trenches gradually coalesce when DBRs grow. Meanwhile, the experimental reflectivity spectra get closer to the simulated results. Finally, we obtain a smooth-surface 25-pair Al.32 Ga.68 N/GaN DBRs with a reflectance of 94% at 390 nm and a 16 nm stopband bandwidth. The preparation of high-quality DBRs lays the foundation for the future development of high efficiency resonant cavity UV LEDs.